1984
DOI: 10.1111/j.1348-0421.1984.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Effect of Chitin and Chitosan on Experimentally Induced Murine Candidiasis

Abstract: Chitin and chitosan were found to exhibit a protective effect on mice administered these polysaccharides intraperitoneally against infection of the viable cells of Candida albicans NIH A‐207 strain. A significant difference was observed between the protective effects of chitin and chitosan, i.e., chitin was much more effective than chitosan when the C. albicans cells were challenged via the intravenous route. In intraperitoneal inoculations of C. albicans cells, however, chitosan provided stronger resistance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 27 publications
5
44
0
1
Order By: Relevance
“…Furthermore, the number of PMN increased significantly in both types of tumor-bearing mice. It is well known that active oxygen intermediates are important candidacidal factors (12). Our results showed that the contents of PMN active oxygens increased in ascites tumor-bearing mice compared to in normal control mice.…”
Section: Notessupporting
confidence: 60%
“…Furthermore, the number of PMN increased significantly in both types of tumor-bearing mice. It is well known that active oxygen intermediates are important candidacidal factors (12). Our results showed that the contents of PMN active oxygens increased in ascites tumor-bearing mice compared to in normal control mice.…”
Section: Notessupporting
confidence: 60%
“…Rementería et al (233) extended the earlier studies to examine chitin purified from the C. albicans cell wall. They reported that, as observed by Suzuki et al (279), injection of mice with purified C. albicans chitin (30 mg kg Ϫ1 ) increased the survival time in response to a C. albicans challenge of 10 5 cells. In these experiments, it was explicitly stated that control mice were given an injection of saline to control for the stress of the injection itself.…”
Section: Immune Cell Receptors and Interactionsmentioning
confidence: 60%
“…Suzuki et al (279) first reported the immunological effects of chitin in a murine model of candidiasis. Mice receiving pretreatment with chitin (50 mg kg Ϫ1 ) were better able to survive a lethal challenge with C. albicans than were mice receiving no treatment.…”
Section: Immune Cell Receptors and Interactionsmentioning
confidence: 99%
“…It shows similarity in the basic molecular structure of hyaluronic acid and is distinguished by its biological properties such as anti-bacterial action and atoxicity [12][13][14], make it an excellent agent for the prevention of postoperative adhesions. For clinical use, it is essential that Carboxymethyl Chitosan (CMC) be submitted to a sterilization process.…”
Section: Introductionmentioning
confidence: 99%